Tax, law and development - Brauner, Yariv; Stewart, Miranda (Cheltenham Edward Elgar Publishing Ltd., 2013)
Summary: Comprising original essays written by top legal scholars, this innovative volume is the most comprehensive collection to date of independent academic work exploring the relationship between tax law and development. Contributors cover a range of tax issues, drawing on economic, political, social, and institutional perspectives to offer a comprehensive view of how tax laws affect and are affected by the process of human economic development. Hailing from across the globe, contributors offer expert insight into tax issues in China, Brazil, South Africa, India, and other developing countries. Topics discussed include tax laws and globalization, tax incentives and foreign investment, tax equity and aid, and transnational tax law and administration. Following a thorough examination of current policy approaches to tax problems in developing nations, the writers conclude that new solutions are needed, and outline a number of groundbreaking ideas and proposals designed to mitigate many of the problems associated with tax law and economic development. Professors, students, and researchers with an interest in tax law, development, and globalization will find much to admire in this critical and groundbreaking addition to the literature."
Foreward / Stephen E. Shay --
Part I Introduction : Taxreform and financing for development / Yariv Brauner and Miranda Stewart --
1. Introduction : Tax, law and development / Yariv Brauner and Miranda Stewart --
Part II Tax competition and tragic choices --
2. The future of tax incentives for developing countries / Yariv Brauner --
3. The tragic choices of tax policy in a globalized economy / Tsilly Dagan --
4. Economic development and the role of tax in Southern Africa : the South African headquarter company structure / Tracy Gutuza --
5. Tax sparing : a reconsideration of the reconsideration / Luis Eduardo Schoueri --
Part III : In Searchers' searchers' to find unique solutions to common tax challenges --
6. Is this a pipe? : Validity of a tax reform for a developing country / Ana Paula Dourado --
7. The place of law in the evolution of Chinese fiscal federalism / Wei Cui --
8. The globalization of tax expenditure reporting : transplanting transparency in India and the Global South / Lisa Philipps --
Part Iv : Tax equity, redistribution and aid --
9. Internation equity and human development / Anthony C. Infanti --
10. The role of developed world tax incentives in microfinance / Charlene D. Luke --
Part V : Tax cooperation --
11. Geographical boundaries of tax jurisdiction, exclusive allocation of taxing powers in tax treaties and good tax governance in relation with developing countries / Pasquale Pistone --
12. Tax activists and the global movement for development through transparency / Allison Christians --
13. Global tax information networks : legitimacy in a global administrative state / Miranda Stewart --
Summary from the British Library Catalogue
Includes bibliographical references (p. 345-375) and index.
Keywords: Law of public finance; TAX LAW; TAXATION; LEGISLATION; INTERNATIONAL ECONOMIC RELATIONS; DEVELOPING COUNTRIES